RANCANG BANGUN PERINGATAN DINI KEBAKARAN RUMAH BERBASIS INTERNET OF THINGS - Wanda; Anggi Yulistia; Muhammad Rusdi (Politeknik Negeri Medan, 2021)
Urban areas have densely populated housing, which can cause problems in the event of a fire. The problem that often occurs is that when a fire occurs, the fire department often arrives late, so that the losses due to the fire are even greater. Based on these problems, the authors want to design a House Fire Early Warning System Design Based on the Internet of Things, which is a prototype of a fire early warning tool as a medium of information. In this tool, the system designed is a fire detection system that works in real time and also knows the location of the fire. This system uses a fire sensor (KY-026), a smoke sensor (MQ-2) and a temperature and humidity sensor (DHT 11), based on the NodeMCU microcontroller to detect the presence of fire, smoke and fire temperature. The data received from the three sensors will be sent to the server using NodeMCU. This system utilizes the Telegram Bot and Website as an interface to provide location information to the nearest fire department by displaying it on the Mapbox and the LED lights up as an indication of a fire and a buzzer sounds to alert the home owner.